FREE TRADE ZONE (FTZ) TANJUNGPINANG DALAM KERANGKA EKONOMI POLITIK KELEMBAGAAN - Andini, Sri Putri; Prastya, Imam Yudhi; Safitri, Dian Prima (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2018)
It has been around 10 years since the enactment of government regulations as the basis for the implementation of the free trade zone policy, but until now the reality that occurred is far from ready, this can be seen from the provision of infrastructure which is an important part in supporting the course of the policy but not yet available. In addition to infrastructure, what is no less important is how the institution in this implementation is able to run the existing system. This study uses a qualitative approach with a type of descriptive research. Research locations are in Tanjungpinang City. The results of the study indicate the complexity of the problems experienced by the Institutions of the Zone Council and the Concession Board of the Bintan Region Free Trade Zone and Free Port, so it is not surprising that it ultimately has implications for operational policies. Because the presence of institutions is a determinant of whether a policy is going well or not.